Doomed to fail. The adoption of gendered party finance in Italy at an inhospitable time. Issue 3 (2nd July 2020) - Feo, Francesca; Piccio, Daniela R.
ABSTRACT: Italy stands out as one of the few countries in Europe to have introduced policies linking public funding for political parties to measures to enhance women's political representation. However, such policies have proved to be flawed, failing to meet the objectives that they aimed to address. Starting from these observations, this paper opens the 'black box' of the policy cycle and analyses the stage of policy formulation that led to gendered party finance, to understand why such ill-defined measures were introduced in the first place. In order to do so we retrace, first, the 'support structure' for the adoption of gender representation policies, and identify the relevant elite arena in which the policy was initiated. Then, by analysing parliamentary votes and speeches, we analyse the alliances and the conflict that originated around the policy. We find that, if structural conditions prevented the adoption of a more intrusive policy, its poor design seems to have been the result of the weakness of the support structure for the introduction of feminist policies and of the lack of cross-party alliances among women MPs that might otherwise have promoted the legitimacy of affirmative action.